Keeping diabetes in the family: Lessons from a family with HNF-1α MODY - Selwood, M; Owen, K (2008)
Establishing a precise diagnosis of the aetiology of diabetes can impact on treatment and prognosis and provides information for other family members about their risk of developing diabetes. Maturity-onset diabetes of the young (MODY), part of the differential diagnosis of diabetes presenting in children and young adults, is most commonly caused by mutations in the hepatocyte nuclear factor 1 alpha (HNF-1α) gene. Although many families display the classic diagnostic criteria of autosomal-dominant family history and age of onset before 25 years, frequently diagnostic confusion arises with both type 1 and type 2 diabetes and this can lead to considerable delay in arriving at the correct diagnosis. This family case study is based on a proband found to have MODY due to an HNF-1α mutation after doubts were raised about the aetiology of her diabetes 23 years after the original diagnosis. It illustrates many features of the presentation, investigation and potential problems associated with the diagnosis and management of HNF-1α. It also demonstrates the challenges involved in detecting rare forms of diabetes and the far-reaching effects that making such a diagnosis has on the family as a whole. The difficulties encountered in detecting the proband's true aetiology in this case suggest that more systematic pathways should be in place at or close to diagnosis for identifying monogenic forms of diabetes. Copyright © 2008 FEND.